POLITIK LUAR NEGERI INDONESIA DAN ISU KEAMANAN NON-TRADISIONAL - Alami, Athiqah Nur (Jurnal Penelitian Politik, 2016)
Non-traditional security issues have become Indonesian foreign policy agenda since the last two decades. It is influenced by the Cold War and the growing strength of non traditional security threats that are transnational and endanger the life of people. The non traditional security threats include climate change and environmental destruction, energy security, international migration, and international terrorism. As part of international community, Indonesia is also unavoidable from non-traditional security threats that require the handling of not only domestic policy but also foreign policy. To that end, this paper will examine the importance of non-traditional security issues in Indonesian foreign policy.